What's Cooking : Digital Transformation of the Agrifood System - Schroeder, Kateryna; Lampietti, Julian; Elabed, Ghada (Washington, DC: World Bank, 2021)
The digital agriculture revolution holds a promise to build an agriculture and food system that is efficient, environmentally sustainable, and equitable, one that can help deliver the Sustainable Development Goals. Unlike past technological revolutions in agriculture, which began on farms, the current revolution is being sparked at multiple points along the agrifood value chain. The change is driven by the ability to collect, use, and analyze massive amounts of machine-readable data about practically every aspect of the value chain, and by the emergence of digital platforms disrupting existing business models. All this allows for drastically reduced transaction costs and pervasive information asymmetries that plague the agrifood system. The success of the digital transformation, however, is not guaranteed as the risks it brings are numerous, including those related to data governance and inadequate competition within and between digital platforms. What’s Cooking: Digital Transformation of the Agrifood System investigates how digital technologies can accelerate the transformation of the agrifood system by increasing efficiency on the farm; improving farmers’ access to output, input, and financial markets; strengthening quality control and traceability; and improving the design and delivery of agriculture policies. It also identifies a key role for the public sector in maximizing the benefits of this process while minimizing its risks, through enabling an innovation ecosystem featuring open datasets, digital platforms, digital entrepreneurship, digital payment systems, and digital skills and encouraging equitable technology adoption.